The Bad Impact of Beauty Standard in American Culture in Reasons to be by Neil LaBute - Refsi Fatri Yarni; Delvi Wahyuni (English Language and Literature, 2022)
This thesis is an analysis of the Drama Reasons to Be Ptetty (2008) by Neil LaBiute. The purpose of this analysis is to expose the issue of beauty standard impact in American culture.  This analysis is also intended to expose how the contribution of fictional elements (character and action/plot) in revealing the form of the bad impact of beauty standard in American Culture. This analysis is related to the concept of feminism by Naomi Wolf.. The result of this analysis shows the female character gets the bad impact of beuaty standard which are discriminiation and oppression.